Inappropriate glucagon and GLP-1 secretion in individuals with long-standing type 1 diabetes: effects of residual C-peptide - Thivolet, Charles; Marchand, Lucien; Chikh, Karim (Diabetologia, 2019)
Aims/hypothesis Recent studies have demonstrated that residual beta cells may be present in some people with long-standing type 1 diabetes, but little is known about the potential impact of this finding on alpha cell function and incretin levels. This study aimed to evaluate whether insulin microsecretion could modulate glucagon and glucagon-like peptide-1 (GLP-1) responses to a mixed meal tolerance test (MMTT). Methods Adults with type 1 diabetes onset after the age of 15 years ( n = 29) underwent a liquid MMTT after an overnight fast. Insulin microsecretion was defined when peak C-peptide levels were >30 pmol/l using an ultrasensitive assay. Four individuals with recent-onset type 1 diabetes were included as controls. Glucagon and GLP-1 responses were analysed according to C-peptide patterns. Results We found comparable peak values, Δ 0–max levels and AUCs of glucagon and GLP-1 responses in C-peptide-positive participants ( n = 9) and C-peptide-negative participants ( n = 16) with long-standing diabetes and in participants with recent-onset diabetes ( n = 4). Mean glucagon levels, however, differed ( p = 0.01). Mean GLP-1 responses were significantly lower according to C-peptide positivity ( p < 0.001, ANOVA). Interestingly, GLP-1 levels correlated to glucagon values in C-peptide-positive participants with long-standing diabetes (Pearson’s r = 0.915, p = 0.004) and in participants with recent-onset diabetes ( p < 0.001) but not in C-peptide-negative participants. Conclusions/interpretation The glucagon response to an MMTT in people with long-standing type 1 diabetes is not reduced by the presence of residual beta cells. The reduction of GLP-1 responses according to residual C-peptide levels suggests specific regulatory pathways.